Exploring QSAR, molecular docking, molecular dynamics and pharmacokinetics for 3,4-Dihydro-2H,6H-pyrimido[1,2-c][1,3]benzothiazin-6-imine derivatives targeting Plasmodium falciparum dihydroorotate dehydrogenase - Naveen Dhingra; Aman Mourya; Harlal Singh; Navnit Prajapati (Discover Chemistry)
Abstract Malaria remains a significant global health threat, particularly affecting vulnerable populations in resource-limited regions. Plasmodium falciparum, the deadliest malaria parasite, has developed resistance to existing antimalarial drugs, necessitating the search for novel therapeutic strategies. This study explores the potential of 3,4-Dihydro-2H,6H-pyrimido[1,2-c][1,3]benzothiazin-6-imine derivatives as inhibitors of Plasmodium falciparum Dihydroorotate Dehydrogenase (PfDHODH), a crucial enzyme in the parasite's pyrimidine biosynthetic pathway. The investigation involves Quantitative Structure–Activity Relationship (QSAR) analysis, molecular docking, molecular dynamics simulations and pharmacokinetics studies. The dataset comprises 43 derivatives, recognized PfDHODH inhibitors, and their inhibitory activities guide the QSAR model development. Molecular docking predicts binding interactions, aiding in understanding potential inhibitory mechanisms. Molecular dynamics simulations provide a dynamic perspective on ligand–protein complexes' stability and conformational changes over time. The QSAR model, with an equation predicting anti-PfDHODH activity, demonstrates high accuracy ( $$R^{2}$$ R 2 = 0.92). Structure–activity relationships reveal insights into molecular features influencing antimalarial potency. Molecular docking studies revealed that compounds bind within the active site and active amino acids. In-silico pharmacokinetics studies suggest the favorable therapeutic potential of compounds, supported by acceptable values for human oral absorption and molecular weight. Molecular dynamics simulation showed that compound 31 and 01 remained within an acceptable RMSD values indicating stable interactions with the active site. The study's multidimensional approach provides important insights for designing potent antimalarial agents against drug-resistant Plasmodium falciparum strains.